Empirical study on the impact of working capital management on going concern of manufacturing firms in Ghana - Abednego Osei; Andrew Osei Agyemang; Joseph Owusu Amoah; Inusah Sulemana (Cogent Business & Management, 2023)
Businesses strive for effective working capital management (WCM) since ineffective WCM influences firms' failure in developing economies. However, the connection between WCM and the going concern of firms has not received significant quantitative attention. Hence, this study examines the impact of WCM on the going concern of manufacturing businesses in Ghana. The study goes beyond the edges and fills the literature gap on WCM and going concerns. Using panel data for 55 large-scale manufacturing companies in Ghana from 2002 to 2022, the study employed the Fixed Effect as the main estimation technique and the Random Effect as the robustness test estimator. The findings affirm the need for working capital management since it influences the going concerns of manufacturing firms. Hence, it is recommended that measures including effective mobilization of inventories, cash, debtors, and creditors should be the main motive of management and owners of the business.
Keywords: 650; Working capital management; going concern; manufacturing firms; business management